Leadership Competency in Human Services Organizations From Social Work Administration Perspective - Eka Nurwahyuliningsih; Soni Akhmad Nulhaqim; Hadiyanto A Rachim (Universitas Muhammadiyah Gorontalo, 2023)
Leadership is the ability possessed by a person to be able to influence individuals and groups, so that being a leader is not enough to just rely on talent or experience, but leaders must have competencies that are able to encourage success in achieving organizational goals in providing social services. The writing of this article aims to describe leadership competencies according to the perspective of social work administration in human service organizations. This study is based on literature studies on various credible and up-to-date reference sources consisting of 27 scientific articles and 4 books. This article underscores the importance of competence for a social work administrator (leader), which includes knowledge, professional attitudes, and actions. The results of other studies found that not only the three aspects, but there are additional competencies such as values, traits and emotional intelligence. This competency is something that is absolutely owned by a leader, and is able to assist leaders in facing future challenges. In addition, leadership competencies can be used as a self-assessment for leaders in social work practice to improve the performance of human service organizations effectively and efficiently.